Cyberbullying victimization and nonsuicidal self-injury in adolescents: The role of maladaptive schemas and dispositional mindfulness. (August 2021) - Faura-Garcia, Juan; Orue, Izaskun; Calvete, Esther
Abstract: Background: Previous research has found associations between cyberbullying victimization and nonsuicidal self-injury (NSSI) in adolescents. Exploration of the possible mediating variables involved is necessary to support intervention with victims. Objective: This study examined whether depression and early maladaptive schemas (EMS) mediate the association between cyberbullying victimization and NSSI, along with the potential protective role of dispositional mindfulness. Participants and setting: A total of 742 Spanish adolescents (50.20% girls) between 12 and 17 years old (M = 14.58; SD = 1.00) participated in the final sample. Method: Participants completed measures of cyberbullying victimization, NSSI, EMS, depression, and mindfulness facets. Mediational models moderated by facets of mindfulness were tested. Results: Cyberbullying victimization was associated with NSSI through increased depression and EMS. Acting with awareness buffered the association between cyberbullying victimization and NSSI, whereas non-judging increased the association between cyberbullying victimization and depression. Conclusions: Cybervictimization is associated with NSSI. The mindfulness facet of acting with awareness plays a protector role. Interventions in NSSI and cyberbullying could benefit from these findings.